The non-designer's design book : design and typographic principles for the visual novice. - Williams, Robin, ....- (Berkeley : Peachpit, 1994)
1.The Joshua Tree principle 2.Proximity 3.Alignment 4.Repetition 5.Contrast 6.Review 7.Type (& life) 8.Categories of type 9.Type contrasts 10.So, do you get it? 11.Answers to quizzes 12.Bibliography 13.Typefaces in this book
Keywords: Typografie